2022
DOI: 10.3390/jpm12060871
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvascular Changes in Familial Hypercholesterolemia: Analysis with Swept-Source Optical Coherence Tomography Angiography

Abstract: Familial hypercholesterolemia (FH) is a common but underdiagnosed genetic disorder affecting cholesterol metabolism, leading to atherosclerotic disease. The relationship between retinal microvascular changes and the presence of atheroma in patients with FH (FH group), and in comparison to volunteers without FH (CT group), needs further investigation. This cross-sectional study was conducted in a university hospital between October 1, 2020 and May 31, 2021. Cardiovascular data, including the Coronary Artery Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…We noticed that FAZ enlargement occurred in both the FH group and the HoFH group. This result was consistent with the previous observation of retinal ultrastructure changes in FH patients [8,19]. Other studies also revealed that the FAZ area is sensitive to ischemia and oxygen supply insu ciency in several retinal ocular diseases, such as retinal vein occlusion and diabetic retinopathy [21][22][23].…”
Section: Multivariate Regression In Groupsupporting
confidence: 93%
See 3 more Smart Citations
“…We noticed that FAZ enlargement occurred in both the FH group and the HoFH group. This result was consistent with the previous observation of retinal ultrastructure changes in FH patients [8,19]. Other studies also revealed that the FAZ area is sensitive to ischemia and oxygen supply insu ciency in several retinal ocular diseases, such as retinal vein occlusion and diabetic retinopathy [21][22][23].…”
Section: Multivariate Regression In Groupsupporting
confidence: 93%
“…For the DCP, VDs in the DCP segment were signi cantly increased in some subsectors of the parafoveal area in FH patients. This result was consistent with Eid's study of retinal microvascular changes in FH patients [19]. As we noticed in our previous study, a phenomenon occurs in which there is a compensative increase in blood supply in the outer layer of the retina due to the capillary blood supply in the inner layer retina being insu cient, and the increase in the DCP VD may occur before a signi cant difference occurs [24].…”
Section: Multivariate Regression In Groupsupporting
confidence: 93%
See 2 more Smart Citations
“…Second, as for many other OCT-A studies, we showed that age was a major confounding factor that must be considered when interpreting retinal microvascular changes [ 24 ]. Both groups showed similar demographic characteristics, limiting the impact of age on the OCT-A comparison, but many other systemic features can impact a retinal microvascular quantitative analysis such as hypertension, hypercholesterolemia, systemic neurovascular, or cardiovascular disease [ 31 , 32 , 33 ]. Third, the general health characteristics of the control group were self-reported.…”
Section: Discussionmentioning
confidence: 99%